Research on quality of health care from the Mexican Social Security Institute. A bibliometric study. - Susana Navarrete-Navarro; Alejandro Gómez-Delgado; Carlos Riebeling-Navarro; Gloria Araceli López-García; Arnulfo Nava-Zavala (Instituto Nacional de Salud Pública, 2013)
Objective. To identify studies on quality of health care in the IMSS. Materials and methods. A bibliometric, descriptive cross-sectional and retrospective study was conducted, from 1992 to 2011. Results. We identified 881 research studies related to the issue of quality (CI95% 10.6-12.0) of 7 762  studies presented at the annual research meetings. 10 521 articles were published in this period of time and only 946 (CI95% 8.4-9.5) were linked to the issue of quality. Conclusions. The results of this study allowed us to identify the interest about research on quality. Further research is needed to establish what has been the impact on the improvement of quality in health care.